2018
DOI: 10.1016/j.ijpe.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the business and social networks in the domain of production by merging the data from heterogeneous internet sources

Abstract: People, companies, and institutions form networks as part of their technical, economic, and social activities. As a consequence, these networks have an influence on how companies conduct business. Recently, the Internet, professional, and scientific social networks have contributed to the ease and simplicity of the network forming process and the public availability of the corresponding data. We investigate whether useful information about the relationships between individuals, companies, and institutions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Data has become one of the most valuable assets for modern organisations (Weerakkody et al, 2017;Kozjek et al, 2018;Albergaria and Jabbour, 2019). Moreover, organisations are becoming increasingly digital, and as a result a large volume of data is being generated in their supply chains (Sheng et al, 2017;Tan et al, 2017;Akter et al, 2017;Ji-Fan Ren et al, 2017;Ivanov et al, 2019a;Frank et al, 2019;Dolgui et al, 2019a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Data has become one of the most valuable assets for modern organisations (Weerakkody et al, 2017;Kozjek et al, 2018;Albergaria and Jabbour, 2019). Moreover, organisations are becoming increasingly digital, and as a result a large volume of data is being generated in their supply chains (Sheng et al, 2017;Tan et al, 2017;Akter et al, 2017;Ji-Fan Ren et al, 2017;Ivanov et al, 2019a;Frank et al, 2019;Dolgui et al, 2019a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Through integrating the data from heterogeneous Internet sources, Kozjek et al (2018) identified market and social networks in the development field. The article illustrates the utilization of modern computing techniques and data analytics to classify publicly accessible, organized and unorganized, and heterogeneous data networks of individuals, enterprises, and organizations.…”
Section: Related Workmentioning
confidence: 99%
“…This section demonstrates the use of a conceptual framework on the selected studies of introducing data analytics in manufacturing systems. Five existing case studies of developing data-analytics solutions in manufacturing systems, i.e., (Kozjek et al 2017a(Kozjek et al , 2017b(Kozjek et al , 2018a(Kozjek et al , 2018bVrabič, Kozjek, and Butala 2017), are selected. Data-analytics solutions developed within these projects are either innovative ways of reducing the incompleteness of information and discovering new knowledge through additional use of data or they enable the more efficient reduction of information incompleteness than the conventional approaches.…”
Section: Demonstrating the Use Of A Conceptual Framework On Selected Studiesmentioning
confidence: 99%
“…Title, Description, and Mapping 5 Title: Identifying the business and social networks in the domain of production by merging the data from heterogeneous internet sources (Kozjek et al 2018a) Description: It is demonstrated that relevant information about the structures of networks that connect individuals, companies, and institutions for the domain of production can be obtained by merging publicly available internet data using a combination of advanced computational methods including web crawling, machine learning, and creating mash-ups of publicly available services. The feasibility and the applicability of the approach are shown for a case in the automotive domain and a case of the scientific community consisting of people from industry and academia.…”
Section: Disclosure Statementmentioning
confidence: 99%